Kuri: A Simulator of Ecological Genetics for Tree Populations. (26th July 2009) - Alle, Benn R.; Furtado-Alle, Lupe; Gondro, Cedric; Magalhães, João Carlos M.
Abstract : This paper presents Kuri, a software package developed to simulate the temporal and spatial dynamics of genetic variability in populations and multispecies communities of trees, as well as their interactions with environmental factors. A conceptual model using agents inspired on Echo models is used to define the environment, the hierarchical structures, and the low-level rules of the system. At the individual agent (tree) level a genetic algorithm is used to model the genotypic structure and the genetic processes, from a small set of simple rules, complex higher-order population, and environmental interactions emerge. The program was written in Delphi for the Windows environment, and was designed to be used for educational and research purposes.